Subjective brain fog: a four-dimensional characterization in 25,796 participants - Alim-Marvasti, Ali; Ciocca, Matteo; Kuleindiren, Narayan; Lin, Aaron; Selim, Hamzah; Mahmud, Mohammad (Frontiers in Human Neuroscience, 2024)
What are the correlates of subjective brain fog as a syndrome, and can it be homogenously characterized?• Findings: In this large study of 25 796 participants, self-defined brain fog was well characterized using the four dimensions of demographics (females, older mean age 35.7 ± 11.9 years), symptoms and functional impairments (difficulty focusing, concentrating, following conversations, remembering appointments), comorbidities (mainly COVID-19, migraines, concussions, but also anxiety, depression and poor sleep), and objective cognitive function (0.1 standard deviations worse, with the largest deficit in cognitive flexibility and ability to inhibit cognitive interference: 0.13 standard deviations worse, p<0.0001).No problems concentrating stratified a minority of individuals with brain fog into a less functionally impaired group. • Meaning: Brain fog sufferers exhibited surprisingly homogenous symptoms and impairments with significant overlap with migraine disability scores. Brain fog symptoms should be explored by taking a migraine, COVID-19, and concussion history and addressing a combination of treatable comorbidities and lifestyle factors.